Sarcopenic obesity predicts instrumental activities of daily living disability in the elderly - Baumgartner, R.N; Wayne, S.J; Waters, D.L; Janssen, I; Gallagher, D; Morley, J.E (Obesity (Silver Spring, Md.), 2004)
Objective: To determine the association of sarcopenic obesity with the onset of Instrumental Activities of Daily Living (IADL) disability in a cohort of 451 elderly men and women followed for up to 8 years. Research Methods and Procedures: Sarcopenic obesity was defined at study baseline as appendicular skeletal muscle mass divided by stature squared <7.26 kg/m2 in men and 5.45 kg/m2 in women and percentage body fat greater than the 60th percentile of the study sample (28% body fat in men and 40% in women). Incident disability was defined as a loss of two or more points from baseline score on the IADL. Subjects with disability at baseline (scores < 8) were excluded. Cox proportional hazards analysis was used to determine the association of baseline sarcopenic obesity with onset of IADL disability, controlling for potential confounders. Results: Subjects with sarcopenic obesity at baseline were two to three times more likely to report onset of IADL disability during follow‐up than lean sarcopenic or nonsarcopenic obese subjects and those with normal body composition. The relative risk for incident disability in sarcopenic obese subjects was 2.63 (95% confidence interval, 1.19 to 5.85), adjusting for age, sex, physical activity level, length of follow‐up, and prevalent morbidity. Discussion: This is the first study, to our knowledge, to indicate that sarcopenic obesity is independently associated with and precedes the onset of IADL disability in the community‐dwelling elderly. The etiology of sarcopenic obesity is unknown but may include a combination of decreases in anabolic signals and obesity‐associated increases in catabolic signals in old age.